Integrated Transcriptomic and Metabolomic Analyses Reveal the Importance of the Terpenoid, Fatty Acid, and Flavonoid Pathways in Rice Cell Death and Defense - Pengfei Bai; Yanfang Liu; Laisa Gomes-Dias; Rachel Combs-Giroir; Shaoxing Dai; Naeyeoung Choi; Yun Lin; Matthew Bernier; Emmanuel Hatzakis; Guo-Liang Wang; Joshua J. Blakeslee (Plants)
Lesion mimic mutants provide unique tools to investigate plant–pathogen interactions, often exhibiting hypersensitive responses in the absence of biotic or abiotic stresses. The overexpression of the S-domain receptor-like kinase gene, SPL11 cell-death suppressor 2 (SDS2), in rice leads to constitutive programmed cell death and enhanced resistance to fungal and bacterial pathogens. However, the mechanisms underlying this broad-spectrum resistance remain unclear. This study integrates transcriptomic and metabolomic analyses of the SDS2-ACT mutant to uncover gene expression and metabolic shifts associated with disease resistance. To identify SDS2-specific physiological changes related to pathogen resistance, leaf tissues from the SDS2-ACT mutant and the Kitkaake WT line were subjected to both transcriptomic and non-targeted metabolic profiling. Transcriptomic analyses identified 1497 differentially expressed genes (DEGs), including up-regulated genes involved in terpenoid and flavonoid biosynthesis, phytohormone signaling, and defense-related pathways (including pathogenesis-related [PR] genes). Metabolomic profiling revealed significant alterations in the accumulation of several compound classes, including putative: terpenoids, phenylpropanoids, phytohormones, fatty acids, and sugars. These changes are likely correlated with the observed cell death and resistance phenotypes in the SDS2-ACT mutant. This study provides an overall landscape of the transcriptomic and metabolomic alterations in a lesion mimic mutant, identifying candidate defense-related genes and metabolites for functional analysis in rice.